Shape measurement of large thickness glass plates with a white-light scanning interferometer using a compensation glass and a fixed reference surface. (21st June 2021) - Zhang, Kaining; Choi, Samuel; Sasaki, Osami; Luo, Songjie; Suzuki, Takamasa; Liu, Yongxin; Pu, Jixiong
Abstract: Conventional white-light scanning interferometers cannot measure exactly large thickness of glass plates because of a great dispersion effect. In this paper a compensation glass plate is used to reduce the dispersion effect. Moreover, a fixed reference surface is added behind the object and four-step measurements are performed. By this method a front surface profile and a thickness distribution of the object can be measured exactly without knowing the refractive index of the object, the thickness of the compensation glass, and dispersion effect containing in the interferometer. Due to the difficulty in scanning the reference surface at a constant speed over a long distance for a large thickness of the object, a piezoelectric transducer stage with a high positioning resolution are utilized together with an additional interferometer which measures the movement of this stage. Experimental results show that the error in thickness measurement is less than 60 nm and 170 nm for 1 mm and 5 mm-thickness glass plates, respectively.